Spatiotemporal Changes in Land Use and Ecosystem Service Values Under the Influence of Glacier Retreat in a High-Andean Environment - Madrigal-Martínez, Santiago; Puga-Calderón, Rodrigo J.; Bustínza Urviola, Victor; Vilca Gómez, Óscar (Frontiers in Environmental Science, 2022)
Glaciers supply multiple ecosystem services that are threatened by climate change. The retreat and disappearance of tropical glaciers is an important dynamic that affects ecosystems and local communities. The knowledge of the impacts of this land-change dynamic on the supply of ecosystem services is lacking. In that sense, the assessment developed can provide evidence about the costs and benefits of promoting at the same time conservation and human well-being. Then, the main objective of this research is to determine the spatial-temporal changes and their effects on the economic value of ecosystem services in a glacial retreat environment. We selected the Marangani district as a study area. It is comprised of the La Raya Mountain range in the Andes. The assessments were carried out across two scales of observation: the municipality and the watershed level. Here, we process spectral information from Landsat Sensor using the Random Forest algorithm in the Google Earth Engine platform to classify 10 biomes. It was carried out over more than thirty years (from 1986 to 2019). After that, ecosystem services provided by the biomes were valued using the transfer method. This research shows that, at the municipality level, almost all the LULCs faced variations over time, and the glaciers had the highest change accumulating a ratio of –85.51%. Whereas at the watershed level, it is observed a higher tendency of land changes in the areas without glaciers, and those with glacier areas count on permanent larger bofedales. At the municipality level, the economic value of ecosystems shows that bofedales and water surfaces are the LULC that supply the highest ESV (~33,000 USD ha-1 yr-1 each). In addition, without the inflation adjustment, the total ESV is on a trajectory of losing ESV (–$9.67106). In the watersheds with glacier retreat, the significant quantity of bofedales and natural grasslands control the fluctuations of ESV. These high-mountain watersheds play an essential role in giving benefits and value to local communities. In general, the municipality level indicates the trajectory of changes in the district, while the watershed scale shows the urgency for implementing spatial conservation actions.